Detecting LHC neutrinos at surface level - Akitaka Ariga; Steven Barwick; Jamie Boyd; Max Fieg; Felix Kling; Toni Mäkelä; Camille Vendeuvre; Benjamin Weyer (Journal of High Energy Physics)
Abstract The first direct detection of neutrinos at the LHC not only marks the beginning of a novel collider neutrino program at CERN but also motivates considering additional neutrino detectors to fully exploit the associated physics potential. As the existing forward neutrino detectors are located underground, it is interesting to investigate the feasibility and physics potential of neutrino experiments located at the surface-level. A topographic desk study is performed to identify all points at which the LHC’s neutrino beams exit the earth. The closest location lies about 9 km east of the CMS interaction point, at the bottom of Lake Geneva. Several detectors to be placed at this location are considered, including a water Cherenkov detector and an emulsion detector. The detector designs are outlined at a conceptual level, and projections for their contribution to the LHC forward neutrino program and searches for dark sector particles are presented. However, the dilution of the neutrino flux over distance reduces the neutrino yield significantly, necessitating large and coarse detector designs. We identify the experimental challenges to be overcome by future research, and conclude that at present the physics potential of surface-level detectors is limited in comparison to ones closer to the interaction point, including the proposed Forward Physics Facility.